Project Based Learning for Children with Special Needs during the Covid-19 Pandemic - Soedjono Soedjono; Munawir Yusuf; Abdul Rahman (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to describe the application of Project-Based Learning (PjBL) to Special School Teachers (SLB) in distance learning (PJJ) for Children with Special Needs. There were 4 aspects that would be measured: (1) the level of teacher's understanding of PjBL, (2) the level of teacher needs for PjBL in PJJ during the covid-19 pandemic; (3) the quality of PjBL learning applied by teachers after attending PjBL training, and (4) the impact of PjBL on the learning outcomes of Children with Special Needs (ABK). This type of research was survey research involving 22 special school teachers in Central Java Province. Data were collected using a semi-closed questionnaire, which was then analyzed using descriptive statistics. The results showed that teachers' understanding of PjBL was sufficient and the teacher's need for PjBL learning during the COVID-19 pandemic was high. The quality of PjBL learning was considered to be better than conventional learning and the implementation of PjBL had a positive impact on the activity and critical thinking-based learning of students with special needs (ABK).